Novel Quantitative Contrast‐Enhanced Ultrasound Detection of Hypoxic Ischemic Injury in Neonates and Infants: Pilot Study 1. (17th December 2018) - Hwang, Misun; Sridharan, Anush; Darge, Kassa; Riggs, Becky; Sehgal, Chandra; Flibotte, John; Huisman, Thierry A. G. M.
Abstract : Objectives: To investigate whether quantitative contrast‐enhanced ultrasound (CEUS) can accurately identify neonates and infants with hypoxic ischemic brain injury. Methods: In this prospective cohort study, 8 neonates and infants with a suspicion of hypoxic ischemic injury were evaluated with CEUS. Results: An interesting trend was observed in the central gray nuclei–to–cortex perfusion ratios. The ratios at the peak enhancement, wash‐in area under the curve, perfusion index, and maximum wash‐in slopes were lower in all of the affected cases compared to the normal group but not statistically significant given the small sample size ( P  = .0571). Additionally, when the central gray nuclei–to–cortex perfusion ratio was plotted for all time points along the time‐intensity curve, it was observed that the affected cases showed a trend that was qualitatively different from that of the normal cases. In the affected cases, the ratio time‐intensity curves either stayed below 1.0 for the entire enhancement period or reached 1.0 close to peak wash‐in before falling just below 1.0 for the remaining period of enhancement. However, in the unaffected patients, there was a steep wash‐in that crossed the 1.0 threshold and remained above 1.0 for most of the enhancement period. Conclusions: Bedside CEUS is an easily obtainable brain‐imaging modality that has the potential to effectively identify infants and neonates with evolving brain injury. A larger prospective study evaluating the correlation between CEUS findings and the reference standard of diffusion‐ and perfusion‐weighted magnetic resonance imaging is needed to establish it as a diagnostic tool.